Diseño de una propuesta financiera en la propiedad horizontal, como mecanismo de control, medición, seguimiento y creación de valor, en Ciudad verde - Soacha - Acosta Moreno, Angela Yurani; Perdomo Alvarado, Maria Andrea (Universidad Antonio Nariño, 2023)
The lack of strategic planning as a mechanism of organizational management leads to poor operational, administrative and financial practices; the project presented below aims to design a financial planning model for the Manzanilla, Pomarrosa and Begonia coownerships located in Ciudad Verde - Soacha; The methodology applied is based on a descriptive research with a mixed approach where a survey was applied to the administrators of these complexes where the strategic management, accounting and financial management and traceability and service were evaluated; the results indicated deficiencies in the processes in charge and a lack of planning of the activities; it is concluded that the management based on the design of budgets to measure the financial performance according to the goals set is a basic component of a good financial plan